A Unique Case Of A Giant Popliteal Artery Aneurysm Presenting As Popliteal Mass - Volteas, Panagiotis (2024)
Introduction: Popliteal artery aneurysms (PAA) can be very challenging, especially in cases of very large PAAs, with a minimal number of case reports published in the literature. Methods: This is a case report of a 68-year-old male patient with hypertension, hyperlipidemia, diabetes, and schizophrenia who was found to have a giant (10x8x6cm) partially thrombosed PAA, treated with interposition polytetrafluoroethylene (PTFE) graft via a posterior approach. Results: Under general anesthesia, the patient was placed in a prone position, and an extended lazy "S" incision was made on the popliteal fossa. After obtaining proximal and distal exposure, the aneurysm sac was skeletonized, preserving the popliteal vein and the tibial nerve. After proximal and distal control was obtained, the patient was systemically heparinized, and the aneurysm sac was opened. Some genicular branches were ligated inside the aneurysm, and part of the aneurysm sac was excised. A 7 mm PTFE graft was used for reconstruction in an end-to-end fashion. Suction drains were placed in the popliteal space, and the fascia and skin were approximated. The patient was discharged home on the 2nd postoperative day on aspirin and statin with ultrasound surveillance. The patient has remained asymptomatic during follow-up with a patent graft. Conclusions: Open surgical repair constitutes the gold standard of care for huge PAAs to prevent distal thromboembolic events and mass pressure effects from the aneurysm. Documentation of additional experience with open repair of huge PAAs would be beneficial and could help clinical decision-making.